Attention bias and alcohol craving: Differential effects via biological sex and mood - Moskal, Katie R.; Dvorak, Robert D.; Burr, Emily K.; El Helou, Gaelle; Cora, Jessica L.; De Leon, Ardhys N.; Leary, Angelina V. (Alcoholism, clinical and experimental research, 2022)
Background Attentional bias (AB) has been linked to alcohol use, mood, and alcohol craving, with key differences across different types of mood and biological sex. However, further exploration of the role of AB across these alcohol variables is needed. The current study examined the relationship between mood and AB as predictors of alcohol craving using ecological momentary assessment (EMA). Exploratory analysis examined these effects as a function of biological sex. Methods Participants (n = 69) from a Midwestern University carried a mobile device for 15 days and provided ratings of momentary mood (positive mood, anxious mood, and sad mood), alcohol craving, and AB. Data were analyzed using a two‐level multilevel regression model, with associations between craving, mood, and AB examined at both the momentary and between‐subjects levels. Results Across assessments, positive and negative moods were positively associated with momentary craving, with AB found to operate differently between men and women. At the within‐subjects level, increases in positive mood among men strengthened the AB‐craving association, while women showed stronger AB‐craving associations when positive mood decreased. At the between‐subjects level, trait‐like sadness led to positive AB‐craving associations for men, however, this was the opposite for women. Similarly, AB‐craving associations were positive and robust for men with trait‐like positive mood but again the opposite was observed for women. Conclusions The findings highlight the importance and nuances of biological sex in the context of mood, AB, and craving. Interventions targeting AB and/or emotion regulation may yield different outcomes for men and women. For females, when positive mood was low (−1SD), momentary attention bias to alcohol was associated with higher alcohol craving in the moment. For males, when positive mood was high (+1SD), momentary attention bias to alcohol was associated with higher alcohol craving in the moment. These findings highlight sex differences in the ways positive mood may influence event‐level cognition‐craving associations, which may shed light on sex differences during the early stages of the addiction processes.